MINAT MENJADI GURU PAI: ANALISIS PADA MAHASISWA PRODI PAI UIN AR-RANIRY BANDA ACEH - Haikal Amar Adzikra; Teuku Zulkhairi; Misnan; Muhibuddin Hanafiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Whether students in the Islamic Religious Education (PAI) Study Program are genuinely interested in a teaching career matters greatly for producing competent, professional Islamic education teachers in the future. Yet in practice, not every PAI student shares the same enthusiasm for becoming a teacher, even though they are enrolled in a program specifically designed to train educators. This study set out to examine how interested students of the PAI Study Program at UIN Ar-Raniry Banda Aceh are in pursuing a career as PAI teachers, and to uncover what shapes that interest. A qualitative descriptive design was applied, involving 14 active students from the 2022, 2023, and 2024 cohorts who were chosen through purposive sampling. Information was gathered by means of in-depth interviews, observation, and documentation, then processed using the Miles, Huberman, and Saldaña interactive model, covering data reduction, data display, and conclusion drawing. Findings show that students' interest fell into three levels: high (57.1%), moderate (21.4%), and low (21.4%). Personal interest, motivation, career aspirations, and self-confidence the internal factors emerged as the strongest drivers, while family support, social surroundings, learning experiences, microteaching, and views on teacher welfare made up the external factors at play. Notably, microteaching turned out to function as more than just a teaching drill; for many students it also served as a moment of reflection and professional self-selection, helping them either reaffirm or reconsider their career direction. These findings add to the broader understanding of career interest among students at Islamic higher education institutions and offer practical input for PAI Study Programs seeking to design better strategies for strengthening students' professional identity and readiness to become qualified PAI teachers.